Democratisation and electoral engineering in post-ethnic conflict societies - Scholdan, Bettina (Javnost (Ljubljana), 2000)
The article explores the theory and practice of constitutional engineering in the context of ethnically fragmented societies. By looking at the way electoral engineering fits into broader concepts of democratic rights and democratisation processes, the tension between representation and stability is presented as an issue of how to combine democratic legitimacy with efficiency in dealing with post-war situations. Historical and cognitive institutionalism might provide a better understanding of how an ethnic community might evolve into a political community than a rational-choice oriented, positive institutionalism prevalent in conflict management studies. The author suggests three criteria for assessing efforts of constitutional engineering in terms of democratic legitimacy without having to solve the dilemma of whether democratic institutions or democratic culture must come first. By closing with a brief analysis of discussions of the electoral system in Bosnia, the article raises practical questions about the rhetoric of institutionalism and democratic theory in a post-war context.
Keywords: država; state; etnične skupine; etnični odnosi; etnični konflikti; demokratizacija; democracy; demokracija; election; volitve; Bosna in Hercegovina; Bosnia and Herzegovina